Implementation of Fresh Food Certification Service Policy of Plant Origin at the Food Quality and Safety Certification Center UPTD in Bali Province - Wayan Aris Surya Darma; Ida Bagus Teddy Prianthara (Publisia: Jurnal Ilmu Administrasi Publik, 2026)
This study aims to analyze the implementation of the Fresh Food of Plant Origin (PSAT) certification service policy at the Technical Implementation Unit (UPTD) of the Food Quality and Safety Certification Center (BSMKP) in Bali Province. The data reveals a significant paradox: a large potential for PSAT production contrasts sharply with a very low and declining realization of certification issuance. Using a qualitative case study approach, data was collected through in-depth interviews with seven key informants (UPTD BSMKP officials, Agricultural Office officials, and business actors) and document studies. Data analysis employed Edward III's policy implementation model, focusing on four variables: communication, resources, disposition, and bureaucratic structure. The findings indicate that policy implementation has procedurally taken place but remains ineffective. Key internal constraints include limited budgetary and facility resources, a partially integrated administrative system, and procedural complexities that hinder efficiency. More crucially, external constraints stem from business actors' perception that certification provides no economic added value, as certified products receive no price premium or special placement in modern retail markets. This study recommends an integrative approach that combines institutional capacity strengthening (through service digitalization and sustained technical assistance) with active market development strategies (through regulations mandating the absorption of certified products, collaboration with retailers, and collective brand building). Consequently, certification can shift from an administrative burden to a strategic instrument for enhancing the competitiveness of Bali's agricultural products